2020
DOI: 10.1371/journal.pone.0228337
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte autophagy is associated with foot process effacement and proteinuria in patients with minimal change nephrotic syndrome

Abstract: Autophagy is a cellular mechanism involved in the bulk degradation of proteins and turnover of organelle. Several studies have shown the significance of autophagy of the renal tubular epithelium in rodent models of tubulointerstitial disorder. However, the role of autophagy in the regulation of human glomerular diseases is largely unknown. The current study aimed to demonstrate morphological evidence of autophagy and its association with the ultrastructural changes of podocytes and clinical data in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 68 publications
1
10
1
Order By: Relevance
“…All these studies suggest a protective role of enhanced autophagy in pathological conditions, further supported by the findings of Adriamycin-induced nephropathy, where autophagy is activated to protect against podocyte injury [ 43 ], as well as in age-dependent glomerular disease where it delays the progressive functional decline of the kidney function [ 40 ]. Analysis of human kidney biopsies also showed evidence of increased autophagy in association with foot process effacement in several glomerular diseases, including minimal change nephrotic syndrome (MCNS), which is one of the most common causes of idiopathic nephrotic syndrome [ 19 ]. In the conditions of diabetic nephropathy and lipopolysaccharide-induced acute kidney injury, enhancing autophagy with some therapeutics through inhibition of the PI3K/AKT/mTOR pathway ameliorates kidney function [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies suggest a protective role of enhanced autophagy in pathological conditions, further supported by the findings of Adriamycin-induced nephropathy, where autophagy is activated to protect against podocyte injury [ 43 ], as well as in age-dependent glomerular disease where it delays the progressive functional decline of the kidney function [ 40 ]. Analysis of human kidney biopsies also showed evidence of increased autophagy in association with foot process effacement in several glomerular diseases, including minimal change nephrotic syndrome (MCNS), which is one of the most common causes of idiopathic nephrotic syndrome [ 19 ]. In the conditions of diabetic nephropathy and lipopolysaccharide-induced acute kidney injury, enhancing autophagy with some therapeutics through inhibition of the PI3K/AKT/mTOR pathway ameliorates kidney function [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, dysfunctional podocytes play a crucial role in glomerular disease, especially in human idiopathic nephrotic syndrome [ 17 , 18 ] and in minimal change nephrotic syndrome (MCNS) [ 19 ]. Hence, autophagy maintains cellular homeostasis under normal physiological conditions, whereas in pathological conditions, it can progress into autophagic death [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data show a strong association between urinary nephrin levels and the extent of (non-selective) glomerular proteinuria, suggesting that hantavirus infection causes a pronounced podocyte damage and subsequent impairment of the GFB. The significant findings in electron microscopy analyses were a focal foot process effacement, podocyte vacuolization and apical tubular vacuolization (indicating massive proteinuria) which all are known as typical histopathological features in INS 16,17,[31][32][33][34][35] . However, the pathomechanical role and underlying mechanisms of the observed podocyte vacuolization need further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed a positive and significant correlation between the density of LC3-labeled podocytes and eGFR. Ogawa-Akiyama el al, demonstrated positive areas of LC3 co-located with positive areas of WT1 in immunofluorescence, suggesting the occurrence of autophagy in podocytes of patients with MCD [ 31 ]. A study with renal biopsies of patients with MCD and with FSGS showed that podocytes from MCD patients had higher levels of Beclin-mediated autophagic activity1 than podocytes of FSGS patients.…”
Section: Discussionmentioning
confidence: 99%